DEFINITION OF METAMORPHISM THERMODYNAMIC CONDITIONS FOR ARMENIAN PRECAMBRIAN KASAKH SUITE BY AMPHIBOLE THERMOBAROMETER (Proceedings of the YSU C: Geological and Geographical Sciences, 2011)
Armenian Precambrian basement rocks metamorphism P and T conditions are defined applying amphibole thermobarometer by means of 104 amphibole microprobe chemical analyses. Measurements have been done on 2 samples of ophiolitic metabasalte amphibolites of the Precambrian Kasakh suite. The general trend of metamorphism has been defined in the average amphibolite and green-schist facies in ranges Т=420–640℃ and P=1,6–5,7 kbr of low geothermal gradient of 12℃/km. Prograde magneziohornblende-tchermakite and retrograde magnezio-hornblende-actinolite zonation has been revealed, and also relics of kersutite have been found. Relics of kersutite are preserved from primary-magmatic hornblende of the initial basalts.
Keywords: Precambrian Kasakh suite; green-schist facies; prograde magneziohornblende-tchermakite; retrograde magnezio-hornblende-actinolite zonation; primary-magmatic hornblende